أثر استخدام الخرائط الذهنیة الالکترونیة فى زیادة تحصیل الطلاب لوحدتین من مقرر مدخل الى تکنولوجیا المعلومات :دراسة تجریبیة على طلاب الفرقة الأولى بقسم المکتبات والمعلومات بکلیة الآداب جامعة طنطا - د.نادیة سعد مرسى (المجلة الدولية لعلوم المكتبات والمعلومات)
The aim of the study was to identify the impact of teaching usingelectronic mind maps in scholastic achievement, as one of the most importantstrategies for active learning among students of the Department of Libraries andInformation at the Faculty of Arts, Tanta University, in two modules of the courseentitled "Introduction to Information Technology" The researcher used theexperimental method and the experimental test as a tool. The study was appliedto experimental group and control after verifying the internal honesty of themembers of the two groups, and the work of a tribal test to ascertain theequivalence of the two groups with the academic achievement. The achievementtest was the end of the semester for the year 2016/2017, after verifying its validityand consistency, distinguishing its expressions and the effectiveness of thealternatives for each term. The result was that the average achievement of theexperimental group using mental maps was higher than the average of the grouptaught in the traditional way. For the difference between mean and statisticalsignificance, the study recommended using mental maps in the teaching ofuniversity courses.